Comparative study of MRS Agar and GYP- Calcium carbonate Agar for Isolation of Lactic Acid Bacteria from indigenous yogurt (Ju Ju Dhau) of Bhaktapur, Nepal - Singh, Arabinda Kumar; Joshi, Jarina; Karki, Roji; Pant, Om; Poudel, Pramod (Patan Prospective Journal, 2025)
Lactic acid bacteria (LAB) are important for food fermentation like yogurt and probiotic use. The isolation and enumeration of Lactic Acid Bacteria (LAB) are fundamental steps in studying the microbial diversity and probiotic potential of traditional fermented Ju Ju Dhau dairy products. LAB play a vital role in the fermentation process by producing lactic acid, which contributes to flavor, texture, and preservation in Ju Ju Dhau of Bhaktapur, Nepal which is king of curd. The present study aimed to investigate the efficiency of MRS (de Man, Rogosa, Sharpe) agar and GYP-Ca agar (Glucose-Yeast-Peptone with CaCO₃) in isolating LAB from fermented food samples. Results showed that while MRS agar offers broad-spectrum isolation, GYP-Ca agar provides selective and cost-effective isolation of strong acid producers through visual detection by halo formation. Samples of indigenous yogurt were serially diluted and cultured on both media under anaerobic conditions at 37oc. The colonies showed convex, creamy colour less than 1mm of LAB morphology. The Gram staining reaction conformed that all Lab are gram positive and catalase negative. Results indicated that both media supported the growth of diverse LAB populations, including species of Lactococcus, Lactobacillus, Leuconostoc, and Pediococcus. However, GYP-Ca agar demonstrated higher selectivity by suppressing non-LAB contaminants and producing clear zones around colonies due to calcium carbonate hydrolyze support to identification. MRS agar, while effective, showed slightly lower colony differentiation and higher background flora.